Propuesta de diseño de un sistema de objetos adaptados a un espacio como estrategia de motivación para los docentes de la Institución Insta - Torres Pilco, Johanna Elizabeth (2018)
In the present work, an object of several entertainment activities was realized, which is focused on the teachers of the Insta Technical Institution. Teachers, when performing different work tasks, are vulnerable to suffer from stress and work pressure as well as to develop a bad work environment, therefore, through User Centered Design, an exhaustive research towards Teachers, taking into account Theories of Design and also observation, as a fundamental tool to find the essential characteristics within this process to meet with the main objective that is to motivate teachers. The project contains information supported in detail of the process acquired during the investigation and its respective analysis, as well as the development of the object in its different phases of design according to the chosen methodology. All the work done, presents the application of different Design Concepts and their respective validation according to each determined process and thus obtain a product that offers entertainment to the user.